Insights into the removal of lithium and molybdenum from groundwater by adsorption onto activated carbon, bentonite, roasted date pits, and modified-roasted date pits - Ayesha Y. Ahmad (14152779) (2022)
This study investigated the removal of lithium (Li) and molybdenum (Mo) from groundwater using activated carbon, bentonite, roasted date pits, and modified-roasted date pits as adsorbents under different experimental parameters including pH, initial concentration, and temperature. Various adsorption isotherm models were used to determine the best-fit model for the obtained experimental data. The negative values of Gibbs energy (ΔG°) indicated a spontaneous and favorable adsorption process of the adsorption at high temperatures. The positive entropy values (ΔS°) that controlled the adsorption process suggested the possibility of some structural changes or readjustments in the adsorbate–adsorbent complex. The adsorption efficiency of Li increases at 35 °C using the four adsorbents. At 35 °C, the maximum adsorption efficiency reached 95% for AC, 94% using MDPs, 63% using bentonite, and 38% using RDPs. The modified-roasted date pits showed the highest adsorption of Mo in all real groundwater samples. The adsorption of Mo increased with the increase in concentrations, and its maximum removal at 25 °C was 80%. Other Information Published in: Bioresource Technology Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.biteb.2022.101045